Alternative technology for the production of squash seedlings using humic substances in the semi-arid region of Bahia (Research, Society and Development, 2022)
Nowadays, the development of low-cost technologies that help the rural producer in raising the productivity of crops with environmental concern is essential. From this, the objective of the present work was to evaluate doses of humic substances as an alternative for the production of squash seedlings. The research was developed at the University of the State of Bahia - UNEB, in Euclides da Cunha - Bahia, using the Moranga Exposure cultivar. The experimental design adopted was completely randomized with 3 compounds and 5 doses, with 15 treatments and 5 repetitions for each compound dose, in a 3x5 factorial scheme. The doses of humic substances used were 0, 0.5, 1.0, 2.0 and 4.0 mL/plant-1. The following variables were analyzed: number of leaves, stem diameter, plant height, chlorophyll content, root length, shoot dry mass and root dry mass. Based on the results found, it was concluded that the dose of 0.5 mL/plant-1 provided squash seedlings with a greater number of leaves (3.4), plant height (25.2 cm), stem diameter (0.68 mm), chlorophyll content (40.1 µg.cm-2), root length (31.40 cm), shoot dry mass (1.78 g), root dry mass (0.35 g). It was also possible to observe that the dose of 4.0 mL/plant-1 and the absence of humic substances in the dose of 0 mL/plant-1 had a limiting effect on the development of the culture. Thus, doses of 0.5 mL/plant-1 are indicated for the production of squash seedlings in the semi-arid region.